2021
DOI: 10.1136/archdischild-2020-321108
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis and SARS-CoV-2

Abstract: BackgroundIt has been speculated that the SARS-CoV-2 was already widespread in western countries before February 2020.MethodsWe gauged this hypothesis by analysing the nasal swab of infants with either bronchiolitis or a non-infectious disease admitted to the Ospedale Maggiore, Milan (one of the first epicentres of SARS-CoV-2 outbreak in Europe) from November 2019.ResultsThe SARS-CoV-2 RNA was never detected in 218 infants with bronchiolitis (95 females, median age 4.9 months) and 49 infants (22 females, media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
(7 reference statements)
3
11
2
1
Order By: Relevance
“…As for bronchiolitis due to SARS-CoV-2, coronaviruses other than SARS-CoV-2 are also sometimes detected in respiratory samples, often presenting as co-infections. However, in contrast to what was reported by Milani PG et al [ 24 ], we did not find any cases of bronchiolitis due to SARS-CoV-2 during the 2019–2020 season. Instead, we identified the first case of SARS-CoV-2-related bronchiolitis in the 15th week of the current season (2020–2021).…”
Section: Discussioncontrasting
confidence: 99%
“…As for bronchiolitis due to SARS-CoV-2, coronaviruses other than SARS-CoV-2 are also sometimes detected in respiratory samples, often presenting as co-infections. However, in contrast to what was reported by Milani PG et al [ 24 ], we did not find any cases of bronchiolitis due to SARS-CoV-2 during the 2019–2020 season. Instead, we identified the first case of SARS-CoV-2-related bronchiolitis in the 15th week of the current season (2020–2021).…”
Section: Discussioncontrasting
confidence: 99%
“…Most children affected by SARS-CoV-2 develop an asymptomatic or mild disease [ 27 , 28 ]. On the other hand, a minority of cases present more severe manifestations such as lower tract respiratory infections (e.g., bronchiolitis or pneumonia) or cardiac diseases, as in the case of multisystem inflammatory system [ 29 , 30 , 31 ]. Recent data showed that the risk of hospitalization for COVID-19 illness in children, including admission to intensive care units, is similar to that of influenza [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on SARS-CoV-2 infection in the paediatric age suggest that, in most cases, children develop a milder disease compared with adults, with hospitalisation or admission to intensive care unit (ICU) being required in only a minority of cases 6. To date, little data are available about the role of SARS-CoV-2 in the development of bronchiolitis in infants and newborns 7 8…”
Section: Introductionmentioning
confidence: 99%